Effect of the conduction band offset on interfacial recombination behavior of the planar perovskite solar cells. (November 2018) - Ding, Chao; Zhang, Yaohong; Liu, Feng; Kitabatake, Yukiko; Hayase, Shuzi; Toyoda, Taro; Yoshino, Kenji; Minemoto, Takashi; Katayama, Kenji; Shen, Qing
Abstract: The effects of the conduction band offset (CBO) between the electron selective layer (ESL) and the perovskite layer in planar-heterojunction perovskite solar cells (PSCs) have been systematically investigated for the first time. To obtain different values of CBO, Magnesium doped zinc oxide (Zn1-x Mgx O (ZMO)) thin films with a tunable conduction band energy level were employed as a model ESL in planar PSCs. We found that the charge recombination at the interface between the ESL and perovskite is strongly dependent on the CBO values: When the cliff structure is formed, i.e., when the conduction band minimum (CBM) of the ESL is lower than that of the perovskite, the interface recombination became dominant, and the open-circuit voltage ( V oc ) worsened. When the spike structure is formed, i.e., when the CBM of the ESL is higher than that of the perovskite, the interfacial recombination is largely suppressed, which leads to an increased V oc of the solar cells. Additionally, we found that an appropriate amount of Mg doping in ZnO to form ZMO reduced carrier concentration and improved carrier mobility, thereby enhancing the charge collection efficiency of the photoexcited electrons by the FTO electrode and, consequently, the short-circuit current density ( J sc ). Using transient absorption (TA) measurements, we have revealed for the first time that the electron injection from photoexcited MAPbI3 to FTO through a ZMO compact layer occurs in the timescale of a few nanoseconds in planar PSCs. PSCs based on the optimized Zn0.9 Mg0.1 O-ESL exhibited a considerable increase ( 35%) in power conversion efficiencies (PCE) compared with that of the control device. Graphical abstract: In planar-structure perovskite solar cells (PSCs), a spike structure is formed between the perovskites and the electron selective layer (ESL), i.e., the energy level of the conduction band of the ESL is higher than that of the perovskite absorber. This spike structure can lead to less photovoltage loss for the PSCs while maintaining high electron injection, which results in a higher open-circuit voltage and a greater short-circuit current, as well as a higher efficiency for planar PSCs. fx1 Highlights: The effects of the conduction band offset have been systematically investigated in planar PSCs for the first time. The conduction band offset adjustment was essential to reduce the interfacial recombination. The photoexcited electron transfer rate from perovskite to electrode in the planar PSCs were revealed.